Regulatory Requirements for the Identification, Detection and Quantification of Gene-Edited Products in Light of the (R)evolution of New Genomic Techniques: State of the Art and Prospects for Changes - Aleksandra Hubar-Kołodziejczyk; Kai P. Purnhagen (European Journal of Risk Regulation)
The key requirement for GMO authorisation is the submission of analytical methods for the detection, identification and quantification (DIQ), which has proven challenging in the case of New Genomic Techniques (NGTs). Currently available non-analytical approaches, such as blockchain traceability and probabilistic analysis, while potentially useful for monitoring, are insufficient for authorisation purposes. The lack of reliable DIQ methods hinders the authorisation of NGT products and raises concerns for both organic and conventional agriculture, where the presence of NGT products goes undetected. Therefore, the existing GMO regulatory framework requires reevaluation to address the challenges posed by NGTs while ensuring compliance with the broader EU food law framework.